THE INFLUENCE OF MOTIVATION, PERCEPTIONS OF PROSPECTIVE STUDENTS, AND UNIVERSITY PROMOTIONS ON INTEREST IN STUDYING UNDERGRADUATE PROGRAMS MEDIATED BY ONLINE LECTURES (EMPIRICAL STUDY: INDONESIAN GO-JEK PARTNERS) - Lizki, Abraham Charis; Pardede, Ratlan (Ridwan Institute, 2024)
The purpose of this study is to investigate the influence of Motivation, Perception, and Promotion of higher education on interest in studying undergraduate programs among prospective students from Go-Jek Indonesia's partners, as well as the mediation role of online lectures in this relationship. Data were collected cross-sectionally from 264 prospective students using a questionnaire as the primary data collection method. The results of the study show that the perception of prospective students has a positive and significant effect on the interest in undergraduate programs. Higher education promotion to prospective students, including the quality of education, reputation, and job prospects of graduates, has proven to have a negative and significant impact on their interest in choosing online lectures. Online lectures mediate the effect of perception and promotion, both directly and through online lecture mediation. This study is expected to provide new insights into the role of Online Lectures in mediating the relationship between motivation, perception, and promotion and interest in study undergraduate programs in universities in Indonesia.